Literature Review: Health Behavior Changes in Heart Disease Patients Based on Smartphone Game Applications: Literature Review: Perubahan Perilaku Hidup Sehat pada Pasien Penyakit Jantung Berbasis Aplikasi Game Smartphone - Wayan Wardiyana; Herawati, Tuti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: changing health behavior in heart disease patients is a complex process and tends to be difficult to carryout. Smartphone game applications can be interactive and fun media as a health promotion effort to support healthyliving behavior in heart disease patients. Objective: to evaluate the use of mobile game applications for healthy livingbehavior in heart disease patients. Method: by searching 10 literatures of research articles related to the topic throughthe online databases including Google Scholar, PubMed, Oxford Journal, ProQuest, Scopus and IEEE. Result: there are10 articles about the use of mobile game-based applications on increasing physical activity and compliance with healthydiet patterns and weight control in heart disease patients. Conclusion: In several aspects, health promotion based onmobile game applications is useful in increasing motivation and commitment to do self-management in heart diseasepatients. Recommendation: smartphone game applications need to be developed, especially to assess effectivenessagainst other aspects related to heart disease risk factors that have not been studied.